Efficient treatment of chronic endometritis through a novel approach of intrauterine antibiotic infusion: a case series - Konstantinos Sfakianoudis; Mara Simopoulou; Yorgos Nikas; Anna Rapani; Nikolaos Nitsos; Katerina Pierouli; Athanasios Pappas; Agni Pantou; Christina Markomichali; Michael Koutsilieris; Konstantinos Pantos (BMC, 2018)
Abstract Background Early diagnosis and efficient management of Chronic Endometritis (CE) in patients seeking fertility treatment are two components every practitioner wishes to address. With respect to endometrial restoration, antibiotic treatment appears to perform well. However, regarding the improvement of In Vitro Fertilization (IVF) success rates, literature evidence is inconclusive, and consensus on optimal treatment has yet to be reached. This manuscript uniquely brings to literature the first report on effective employment of intrauterine antibiotic infusion to treat CE and contribute to addressing the infertility related to it. Case presentation In this case series, we present 3 patients reporting numerous previous failed IVF attempts accompanied with diagnosed CE which failed to be properly treated in the past. Following initial assessment in our clinic and verification of CE findings, an oral antibiotic regime was administered based on the infectious agent detected. Re-evaluation concluded slightly improved microbiological environment in the endometrium but persisting inflammation. Antibiotic intrauterine infusion was proposed to the patients as an alternative practice. All our patients achieved a pregnancy shortly following intrauterine treatment with one patient reporting a live birth of twin babies and two patients currently reporting an ongoing pregnancy. Conclusions The implications of this case series contribute to medical knowledge and extend to both effective treatment of CE and subsequent management of related infertility. The current line of treatment of CE through oral antibiotic regimes highlights the need for exploring new options and calls for larger studies on the clinical implication of their use. This novel approach enabled natural conception for patients presenting with established Recurrent Implantation Failure (RIF) having undergone numerous futile IVF attempts. The clinical impact from the practitioner's perspective is considerable allowing for an alternative line of treatment that merits further investigation.